Role of Ions in the Regulation of Light-Harvesting - Kaňa, Radek; Govindjee, (Frontiers in Plant Science, 2016)
Regulation of photosynthetic light harvesting in the thylakoids is one of the major key factors affecting the efficiency of photosynthesis. Thylakoid membrane is negatively charged and influences both the structure and the function of the primarily photosynthetic reactions through its electrical double layer. Further, there is a heterogeneous organization of soluble ions (K+, Mg2+, Cl-) attached to the thylakoid membrane that, together with fixed charges (negatively charged amino acids, lipids), provides an electrical field. The electrical double layer is affected by the valence of the ions and interferes with the regulation of “state transitions”, protein interactions, and excitation energy “spillover” from Photosystem II to Photosystem I. These effects are reflected in changes in the intensity of chlorophyll a fluorescence, which is also a measure of photoprotective non-photochemical quenching of the excited state of chlorophyll a. A triggering of non-photochemical quenching proceeds via lumen acidification and is coupled to the export of positive counter-ions (Mg2+, K+) to the stroma or/and negative ions (e.g., Cl-) into the lumen. The effect of protons and anions in the lumen and of the cations (Mg2+, K+) in the stroma are, thus, functionally tightly interconnected. In this review, we discuss the consequences of the model of electrical double layer, proposed by James Barber (J. Barber (1980) Biochim Biophys Acta 594:253-308) in light of light-harvesting regulation. Further, we explain differences between electrostatic screening and neutralization, and we emphasize the opposite effect of monovalent (K+) and divalent (Mg2+) ions on light-harvesting and on “screening” of the negative charges on the thylakoid membrane; this effect needs to be incorporated in all future models of photosynthetic regulation by ion channels and transporters.